Tingkat Pengetahuan Wanita Usia Subur (WUS) Tidak Berhubungan Dengan Sikap, dan Perilaku Pemeriksaan Payudara Sendiri (SADARI) - Zulfitriani Murfat (Wal'afiat Hospital Journal, 2021)
Breast cancer is one of the non-communicable diseases that is ranked second in the world that mostly affects women. The cause of high cases of death from breast cancer can occur due to delays in detecting breast abnormalities. One way to detect breast cancer is to perform a breast self-examination (BSE). The correct way to do breast self-examination must be supported by experience and attitude in practicing BSE. This study aims to determine how the level of knowledge, attitudes, and behavior of women of childbearing age relate to breast self-examination. This research is a descriptive-analytic study with a cross-sectional approach. This research was conducted at the Faculty of Medicine, the Universitas Muslim Indonesia using a total sampling technique of 114 people according to the inclusion and exclusion criteria. The results of this study indicate that the majority of respondents are at the age of 18 years (57%) and age 20 years (3%). The level of knowledge to realize as much (69.3%) with good knowledge and as much as (30.7%) with less knowledge. Knowledge of the attitudes and behavior of breast self-examination that is good (53.5%) and less (46.5%), based on the results of the chi-square test shows that there is no significant relationship between the level of knowledge with attitudes and behavior how to do consciously with p-value = 0.482. The conclusion is that there is no relationship between the level of knowledge with the attitudes and behavior of women of childbearing age on breast self-examination (BSE).